Réponses

2013-05-05T11:50:55+02:00

Voilà ce que je viens de trouver, en espérant que tu comprennes:

 

3 / (x-3) (x-12)                                                       = x² - 15x + 36  - (x-3) (x-12)

3 / x² -12x -3x +36                                                = x² - 15x + 36 - x² - 12x - 3x + 36

3 / x² - 15x + 36                                                     = 30x + 72

3                                                                              = -30x +72 / x² -15x + 36

3                                                                              = (-15x X 2 + 36 X 2) /  x² - 15x + 36

3                                                                               = (2 X 2) / x²

3                                                                                = 4 / x²

3x²                                                                             = 4

4/3                                                                            = x²

racine de 4/3                                                           = x

 

j'espère avoir su être à la hauteur! :)